Without standards, but with principles: educating in diversity - Coriñaupa Vargas, Francisco (2020)
From a very young age children are introduced to the world of education, whether for whatever reason, the student before the age of twenty spent most of his or her life in anintentionally built environment for learning. From the above, we can deduce that the enormous influence that the school (institution, curriculum, peers, teachers and even other parents) has on the student and his or her way of perceiving the world, whether as an exclusive world, which he or she has to enter, or as a world that respects diversity. In this sense, success is no longer banal if it does not respond to what society asks for as truth, but is a possibility to build from its peculiarity, respecting the principle of being unique in every sense, hence it is not possible to standardize how one learns. Educating in diversity is an ethical act.